Mechanisms of von Willebrand factor activation driving no reflow in ischemic stroke - Audrée Laroche; Nick Rovito; Alice Liu; Isabelle Allaeys; Laura Heitsch; Irina Portier; Opeolu Adeoye; Stephanie R. Pizzella; James A. Giles; Jorge Di Paola; Jin-Moo Lee; David Bark; et al. (Proceedings of the National Academy of Sciences, 2026)
Rapid restoration of cerebral blood flow is the cornerstone of acute ischemic stroke treatment. Endovascular thrombectomy achieves substantial reperfusion in 90% of patients with large-vessel occlusion stroke; however, almost half of treated patients continue to have significant disability despite successful thrombus removal. Transient periods of ischemia can trigger microvascular thrombosis resulting in the no-reflow phenomenon. Yet the molecular and hemodynamic triggers underlying no reflow remain poorly defined. Using a murine model of transient ischemic stroke combined with intravital imaging, we visualized platelet-von Willebrand factor (VWF) thrombi forming in penumbral tissue where blood flow dynamics were altered in response to the original ischemic insult. In silico modeling based on our intravital observations indicated that the altered, converging blood flow in these vessels increases local elongational flow, a condition that can favor VWF unfolding. The activity of VWF is controlled by ADAMTS13, which cleaves VWF. We further identified that in the acute phase of stroke, locally released IL-6 suppresses ADAMTS13-mediated cleavage of VWF, creating a prothrombotic imbalance that promotes microvascular thrombosis and worsens outcomes in mice. In ischemic stroke patients, we observed an acute increase in IL-6 that correlated strongly with increased VWF activity. VWF activity was highest in patients experiencing worse outcomes. Inhibition of IL-6 in ex vivo stroke patient plasma restored ADAMTS13 activity. Together, these findings reveal how hemodynamic and inflammatory factors converge to favor VWF activation in the reperfused brain and contribute to the development of no reflow in ischemic stroke.